2020
DOI: 10.1136/bmjopen-2020-042090
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 outcomes in UK centre within highest health and wealth band: a prospective cohort study

Abstract: ObjectivesTo describe the characteristics and outcomes of hospitalised patients with COVID-19 from UK in the highest decile of health and gross regional products per capita.DesignProspective cohort study.SettingRecruited all adult inpatients with laboratory-confirmed COVID-19 symptoms admitted to a single Surrey centre between March and April 2020. Extensive demographic details were documented.Outcome measureCOVID-19 status of alive/dead and intensive care unit (ICU) status of yes/no.ParticipantsPatients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
4
11
0
Order By: Relevance
“…23 There are likely numerous reasons for these reported wide variations in HCW seropositivity, including (but not limited to) antibody assays used, time points of testing (eg different phases of the pandemic), distributions of patients (eg into 'COVID-19 hospitals' and 'non-COVID-19 hospitals'), as well as differences in local guidance on, and availability of, personal protective equipment. It should be noted that despite working in a hospital located in an affluent, socially homogeneous and relatively healthy region 7 where seropositivity levels in the general population are low, 12 our HCWs exhibited similar seroprevalence levels to other HCWs working in more deprived areas where the general population was more likely to be seropositive. 12 More than 30% of all non-White staff were found to be antibody positive and we demonstrate that non-White ethnicity confers a significantly increased risk of seropositivity.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…23 There are likely numerous reasons for these reported wide variations in HCW seropositivity, including (but not limited to) antibody assays used, time points of testing (eg different phases of the pandemic), distributions of patients (eg into 'COVID-19 hospitals' and 'non-COVID-19 hospitals'), as well as differences in local guidance on, and availability of, personal protective equipment. It should be noted that despite working in a hospital located in an affluent, socially homogeneous and relatively healthy region 7 where seropositivity levels in the general population are low, 12 our HCWs exhibited similar seroprevalence levels to other HCWs working in more deprived areas where the general population was more likely to be seropositive. 12 More than 30% of all non-White staff were found to be antibody positive and we demonstrate that non-White ethnicity confers a significantly increased risk of seropositivity.…”
Section: Discussionmentioning
confidence: 56%
“…10,11 For individual tests of association, rather than applying a correction for multiple testing at global significance level, statistical significance was defined as 0.01. 7 Analyses and graphics were performed and produced using R version 4.0.0.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,475 records were included in the initial search and 9,369 remained after duplicates were removed. After excluding articles that did not meet the inclusion criteria, 286 studies (including 4 study from references) were full-text screened and finally 149 articles [ [20] , [21] , [22] , [23] , [24] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] <...>…”
Section: Resultsmentioning
confidence: 99%
“…Some of the risk attributed to obesity likely reflects coincident T2D and impaired cardiopulmonary fitness. The relative risk also appears greater in individuals with T2D, suboptimal health care, and in some, but not all, studies, socioeconomic deprivation ( Ken-Dror et al., 2020 ; Sosa-Rubí et al, 2021 ), risk factors less frequently reported in most reports. The pathophysiology of T2D underlying enhanced SARS-CoV-2 pathogenicity remains uncertain, but may be associated with increased rates of coagulopathy underlying enhanced mortality, as described in severely ill, hospitalized people with COVID-19 in Wuhan ( Chen et al., 2020a ).…”
Section: Obesity and Covid-19 Outcomesmentioning
confidence: 94%